A Study of Operational Research Challenges: Exploring and addressing challenges in operational research (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Operational research, also known as operations research, is a field of study that appliesmathematical modeling, statistical analysis, and optimization techniques to solve complex decisionmakingproblems in various domains. This study aims to explore and analyze the challenges faced in thefield of operational research. By identifying and understanding these challenges, researchers andpractitioners can develop effective strategies and approaches to overcome them, leading to improveddecision-making processes and outcomes. This paper provides an overview of the key challenges inoperational research and highlights the significance of addressing these challenges for advancing thefield.